Perlindungan Hukum terhadap Korban Tindak Pidana Pengancaman dan Pemerasan - Beatrix, Anna; Nainggolan, Marsudin; Basuki, Basuki (Universitas Jayabaya, 2023)
Legal protection for victims of criminal threats and extortion is a crucial aspect in ensuring a fair judicial process. This article discusses the challenges and solutions in providing legal protection for victims through a legal and technological approach. Based on an analysis of the Witness and Victim Protection Law, it is found that there are still obstacles in accessing justice for victims, particularly for economically disadvantaged individuals. Moreover, firm law enforcement against perpetrators, the utilization of information technology in handling crimes through electronic media, and enhancing the legal awareness of victims are also focal points in improving the legal protection system. On the other hand, the active role of the Witness and Victim Protection Agency is expected to enhance protection for victims by prioritizing their interests in the judicial process. Through collaborative efforts among the government, protection agencies, and public legal awareness, it is hoped that legal protection for victims can be enhanced to achieve better justice.